TOTAL EDGE IRREGULARITY STRENGTH DARI GRAF K_n-{e} - MUARDI, .; AINI, QURRATUL; IRWANSYAH, , (E-Jurnal Matematika; Vol 7 No 1 (2018), 2018)
In this paper we determine the total edge irregularity strength of , that is a complete graph in which one of its edge has been removed . To do so, we make three cases. In two cases, the labelling of   equals to the labelling of the complete graph  such that no re-label l ing is necessary. Meanwhile, the third case could not happen. As a result, the total edge irregularity strength of  equals to the total edge irregularity strength of Kn